2013
DOI: 10.1016/j.ajpath.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

miR-30a Negatively Regulates TGF-β1–Induced Epithelial-Mesenchymal Transition and Peritoneal Fibrosis by Targeting Snai1

Abstract: Although epithelial-mesenchymal transition (EMT) and the subsequent development of peritoneal fibrosis are key processes leading to the peritoneal failure related to peritoneal dialysis (PD), mechanisms underlying these processes remain largely unclear. In the present study, we found that miR-30a was significantly down-regulated in peritoneal tissues, with progressive fibrosis in patients with continuous ambulatory peritoneal dialysis and in a rat model of PD. In vitro, transforming growth factor (TGF)-β1-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 41 publications
1
107
1
Order By: Relevance
“…19,30 In TGF-beinduced MMT, SNAIL1 was shown to down-regulate CDH1 expression and thereby induce MMT, similar to the mechanism of cancer metastasis. 20,30,33 However, we could not detect CDH1 expression in either peritoneal or liver MCs by immunohistochemistry in mice. 12 Cultured MCs express Snai1 at a low level (data not shown).…”
Section: On the Basis Of The Labeling Efficiency Of Mcs In The Wt1contrasting
confidence: 57%
“…19,30 In TGF-beinduced MMT, SNAIL1 was shown to down-regulate CDH1 expression and thereby induce MMT, similar to the mechanism of cancer metastasis. 20,30,33 However, we could not detect CDH1 expression in either peritoneal or liver MCs by immunohistochemistry in mice. 12 Cultured MCs express Snai1 at a low level (data not shown).…”
Section: On the Basis Of The Labeling Efficiency Of Mcs In The Wt1contrasting
confidence: 57%
“…There are different viewpoints about the relationship between the miR-30 family and the EMT of PMCs. A recent paper reported that miR-30a negatively regulated TGF-β1-induced EMT and peritoneal fibrosis by targeting Snai1 [27]. MGO in the present study and TGF-β1 are two different regulators that induced changes in the peritoneal membrane [13,28].…”
Section: Discussionmentioning
confidence: 62%
“…To achieve Dox-induced transgene expression, pTRE 2 -miR-29b/pTRE 2 -hygro and pEFpuro-p-Tet-on were co-transfected into the abdominal cavity via an ultrasound-microbubble delivery system as described previously with some modifications. 24,25 Briefly, a mixture of plasmids (pTRE 2 -miR-29b or pTRE 2 -hygro EV) and Sonovue (Bracco Diagnostics, Princeton, NJ, USA) was prepared with 1:1 vol/vol ratio. Then the mixed solution containing 200 mg of designated plasmids in total volume of 1 ml was immediately injected into the peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%